PAYING AND SAVING IN GOLD IN THE ROMAN ARMY THE AUREUS OF VESPASIAN FROM RĂZBOIENI-CETATE AND THE EVIDENCE OF GOLD COINS IN ROMAN DACIA (ROMANIA) - Cristian Gazdac; George Bounegru; Rada Varga (Journal of Ancient History and Archaeology, 2020)
Starting from a recently discovered gold coin, aureus, of Vespasian in the military environment of Războieni-Cetate, Romania (in former Roman Dacia), the present study gathered the evidence of similar finds from the territory of former Roman Dacia. A comparative analysis with the evidence from well-documented sites from other Roman provinces (e.g. Britannia) and from ancient literary sources may lead to the conclusion that the military payments could have been made in gold coin, as well as the military would like to keep/save money in the same metal – easy to carry a highest value. Another aspect revealed by this study is the dating of an archaeological context based on numismatic evidence. The coin under study here together with the historical background of the site where it was found indicate that the coin could have been lost almost 30 years later from the date of minting.